Policy and practice in L2 classroom assessment: policy implementation at a state high school in Türkiye - Pınar Yeni-Palabıyık; Ayşegül Daloğlu (Education Inquiry)
This study investigates how the explicit policies set for assessing English achievement in the instructional policy documents come to life at a particular program of a state high school. Junior-year students and their English-as-a-foreign-language teachers were the participants. Data were gathered through field notes, observations, interviews, and documents. Findings suggested a discrepancy between policy and practice in assessing English achievement. Instructional policy documents created at different layers of the policy conveyed a mixture of traditional and performance-based assessment types as the leading features of the intended assessment. However, the field data demonstrated that though principles of intended assessment were achieved to a degree, features of traditional assessment dominated classroom assessment practices. Several contextual factors ranging from teacher beliefs to top-down policy implementation were found influential in the realisation of the policy. The study presents implications for instructional policymaking, language classroom assessment, and in-service training for language teachers.